Growth and Yield of Sesame, Green Gram and Black Gram as Affected by Different Weed Management Practices - Nongmaithem, D.; Pal, D. (International Journal of Bio-resource and Stress Management, 2016)
The experiment was conducted at Instructional farm, Jaguli, Bidhan Chandra Krishi Viswavidyalaya, Mohanpur-741252, Nadia,West Bengal during pre-kharif season in 2010 and 2011 to study the growth and yield of sesame, green gram and black gram due to different weed management practices including the botanical plant extracts. The experiment was conducted in split plot design replicated thrice, keeping the crops under the main plot treatment viz. Sesame, Green gram and Black gram and nine weed management treatments in the sub-plot treatments viz. Untreated control, Hand Weeding at 20 DAS, 5% (w/v) Ageratum conyzoides aqueous extract, 5% (w/v) Blumea lacera aqueous extract, 5% (w/v) Ocimum sanctum aqueous extract, 5% (w/v) Physalis minima aqueous extract, 5% (w/v) Amaranthus tricolor aqueous extract, Quizalofop-p-ethyl 50 g ha-1 at 20 DAS and Fenoxaprop-p-ethyl 30 g ha-1 at 20 DAS. It was found that black gram and green gram recorded higher control of weeds than sesame. Among the weed management treatments, hand weeding recorded highest weed control efficiency which was followed by fenoxaprop-p-ethyl. Among the botanical plant extracts, Ageratum conyzoides extract recorded lowest population and dry weight of sedge and broadleaved weeds while Ocimum sanctum extract recorded the same in case of grassy weeds. Hand weeding recorded the highest yield of all the crops. Among the botanical plant extracts Ageratum conyzoides extract recorded highest growth attributes and yield in sesame and black gram while in green gram, Ocimum sanctum extract recorded highest yield.